Challenges of Pharyngeal Cancer Screening in Lower-Income Countries during Economic and Social Transitions: A Population-Based Analysis - Andreea M. Kis; Claudia G. Watz; Alexandru C. Motofelea; Sorin Chiriac; Marioara Poenaru; Cristina A. Dehelean; Claudia Borza; Ioana Ionita (MDPI AG, 2023)
Background and Objectives: The rate of head and neck cancer (HNC) is expected to increase by 30% by 2030. However, there are many similarities between the symptomatology of a benign and a malign diagnosis; thus, a protocol for conducting a full head and neck examination is of high importance since the absence of adenopathy does not exclude a malignant diagnosis and also a favorable prognosis. Material and methods: The current study presents a retrospective study on 515 adult patients who underwent a biopsy for possible head and neck tumor pathology. Results: The patients identified with cancer were older than the rest of the group, with a higher developing trend in men than in women. However, the top 10 symptomatology patterns were identical in the malign and benign groups, meaning that new HNC may be missed due to the common symptomatology between benign and malign outcomes. Conclusions: The importance of a full ear, nose, and throat (ENT) examination may be of significant relevance for a proper diagnosis that can improve the overall prognosis of a patient with cancer. The absence of routine screening tests and screening guidelines for oral and pharyngeal cancers represents a significant barrier to secondary HNC prevention.